About the Dialectal Forms of Verbs in the Novella “Purva bridējs” (1898) by Latvian Writer Rūdolfs Blaumanis and the Novella Sequel Written in the 21st Century - Liparte, Evija (Acta humanitarica academiae Saulensis, 2026)
The article begins with information about both literary works, writers and their relationship to dialects. The following is a look at the special features of the verbal forms of Blaumanis’ novella “Purva bridējs” (1898) and Nella no Krotes’ novel “Kumeļu sauks Delveris” (2013), which, compared to the dialectological materials of the Latvian language published in the 20th century, was managed to identify as characteristic of one or other dialect of the Latvian language. The following grammatical forms and phenomena have been analysed: 1) The feminine ending -use, (reflexive) -usēs of the past active participle; 2) The no-stem forms of verbs instead the Standard Latvian i̯o-stem forms; 3) A special form būtuot in the subjunctive mood; 4) The non-differentiation of verbal person forms. The first three forms of the verbs are taken from Blaumanis’ novella and must be regarded as a peculiar feature of his native subdialect in Ērgļi and other places in the same Selonic subdialects of the High Latvian dialect. The non-differentiation of verbal person forms (when the 3rd person form is generalized instead of other forms), is a typical feature of the Livonic dialect. A new character introduced into the novel “Kumeļu sauks Delveris” uses it once. Nevertheless, in the works of dialectology, which reflect the dialects of the 2nd half of the 20th century, such forms are also fixed in some places in Selonic subdialects of the High Latvian dialect. However, that data does not support the conclusion that such forms were also used there during Blaumanis’ life, at the end of the 19th century.